2019
DOI: 10.2514/1.c035252
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Wake-Vortex Proximity to Landing Aircraft Exploiting Field Measurements

Abstract: This paper assesses possible wake vortex encounters in lidar field measurements accomplished by DLR and NASA at major international airports (Munich, Frankfurt, Dallas, Denver, Memphis) comprising 8820 aircraft landings. Therefore, the applied separations are analyzed depending on the aircraft pairings and compared to the ICAO and RECAT standards. Further, we evaluate the distances between the wake generated by the leading aircraft and the follower. The results reveal that in 3.6% of the landings with an initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…According to long-term measurements obtained by Doppler LiDARs, at least 3% of wake vortices generated by landing aircraft is within a distance of 25 m to the following aircraft at Charles de Gaulle airport [83]. Körner and Holzäpfel [84] analyzed 8052 aircraft landings recorded by Doppler LiDARs at several international airports, concluding that 3.7% of the landing vortices were generated below 50 m. To artificially accelerate wake vortex decay or destruct wake vortices for the purpose of aviation safety, it is crucial to uncover the physical mechanism of wake vortex decay, particularly during landing phase and the touchdown process. LiDAR observations indicated that continuous vortex decay was associated with strong turbulence [85] while the two-phase decay, i.e., an initial phase of moderate decay followed by a phase of rapid decay, occurred in weakly turbulence environments [86], corroborating the vortex evolution found in corresponding CFD simulations [87].…”
Section: Aircraft Wake Vortexmentioning
confidence: 99%
“…According to long-term measurements obtained by Doppler LiDARs, at least 3% of wake vortices generated by landing aircraft is within a distance of 25 m to the following aircraft at Charles de Gaulle airport [83]. Körner and Holzäpfel [84] analyzed 8052 aircraft landings recorded by Doppler LiDARs at several international airports, concluding that 3.7% of the landing vortices were generated below 50 m. To artificially accelerate wake vortex decay or destruct wake vortices for the purpose of aviation safety, it is crucial to uncover the physical mechanism of wake vortex decay, particularly during landing phase and the touchdown process. LiDAR observations indicated that continuous vortex decay was associated with strong turbulence [85] while the two-phase decay, i.e., an initial phase of moderate decay followed by a phase of rapid decay, occurred in weakly turbulence environments [86], corroborating the vortex evolution found in corresponding CFD simulations [87].…”
Section: Aircraft Wake Vortexmentioning
confidence: 99%
“…These distances are compared to those found within the analysis of lidar measurements and aircraft data described in Ref. 24. The lidar study employs data of 8056 landings collected at the airports Dallas, Denver, Frankfurt, Memphis and Munich.…”
Section: How Conservative Are the Wsvs Predictions Compared To Cmentioning
confidence: 99%
“…We further set the minimum vortex age to 60 s as a value supporting minimum radar separations of 2.5 nm. Operationally WSVS separations below 60 s would not be applicable and adjusted upward to 60 s. In the real-world reference data 24 separation times vary between 80 s and 500 s. Figure 2 illustrates the elements employed in the Monte Carlo simulation conducted for the 78.119 aircraft pairings of the Vienna data base. For the instant of time when all safety corridors do no longer overlap with the aircraft corridors, stochastic aircraft positions and wake vortex positions are generated for the flight altitude of 50 m above ground targeted by the lidar study.…”
Section: How Conservative Are the Wsvs Predictions Compared To Cmentioning
confidence: 99%
“…Speijker et al [11] were the first to propose using roll angular velocity to measure the severity when following aircraft encounters and the wake of preceding aircraft, laying the foundation of the subsequent wake separation reduction research. Holzäpfel et al [12] conducted field detection of aircraft wake by LiDAR. Moreover, the authors performed a safety assessment of wake encounters using the lateral sway control ratio (SSCR) and calculated the critical value of the hazardous SSCR.…”
Section: Introductionmentioning
confidence: 99%